Kānčhatkān nam chumchon phư̄a kǣ panhā namlǣng namthūam nai phư̄nthī nō̜k khēt chonlaprathān (Sathāban Sārasonthēt Sapphayākō̜n Nam læ Kānkasēt, 2012)
Water resources development and water-supply management in Thailand.